Sosialiasi Consumer Behavior Kepada Konsumen Usia Muda: Menjadi Konsumen yang Cerdas - Lermatan, Edwin; Firdaus, Muhammad Iqbal; Widyanto, Prima; Ghafar, Abdul; An, Charles; Octaviani, Reni Dian (Institut Transportasi dan Logistik Trisakti, 2023)
This activity aims to provide socialization to young consumers about understanding the basic concepts of consumer behavior to help increase their confidence in making purchasing decisions as smart consumers. The activity was conducted at SMA 81 Jakarta involving 31 class X students. Pretest and post-test in the form of online questionnaires were administered before and after the socialization. Descriptive analysis and paired t-test were perfomed to analyze the data. The results of the analysis showed an increase in participants' understanding of the concept of consumer behavior in order to become smart consumers. The paired t-test showed that the difference in understanding scores before and after socialization showed a significant increase. The implication of this activity can be the basis for the development of similar extension programs in the educational environment, to equip the younger generation with knowledge and practical skills in dealing with the dynamics of consumer behavior.